Preços das commodities: fatores determinantes e panorama histórico - Santos, Anderson Rodrigues dos (2010)
This work aims to understand what are the main determinants and behavior of commodity prices since the end of the Bretton Woods System , in 1971. Among the main factors usually found in the literature as influential in commodity prices, we have supply expansion resulting from the integration of the soviet cowntries to the world economy, the increase in demand, as a result of economic growth in Asia, particularly China, the interest low levels and exchange rate relationship between the dollar and other reserve currencies and the demand for speculative reason. It also describes changes in the prices of commoditites between 1971 and 2008, enclosed in large frame movements, the first high from 1971 until the shock of Volker, the second of stagnation, due to high interest rates and oversupply commoditites, the third, lift, in response to low real interest rates, rapid economic growth and excess of international liquidity, and finally, the decline, reflecting the effects of global financial crisis in 2007-08. To complement the analysis, commodity prices are arrelated to key macroeconomic variables, to study the behavior of the data, considering the factors mentioned as determinants